2017
DOI: 10.1515/hssr-2016-0008
|View full text |Cite
|
Sign up to set email alerts
|

Challenges, Counselling Needs, and Coping Strategies of Students with Visual Impairment in Regular Secondary Schools in Nigeria

Abstract: This study investigated challenges, counselling needs and coping strategies of students with visual impairment in regular secondary schools in Nigeria. The descriptive survey of cross-sectional design was employed for the study. Five hundred and twenty-seven students with visual impairment in regular secondary schools were included in the survey by using purposive and captive sampling techniques. The findings of the study revealed that the challenges of students with visual impairment in regular secondary scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The findings of the study revealed that the challenges of students with visual impairment in regular secondary schools include inability to access modern technologies, inappropriate teaching methods and non-availability of special curriculum. The studies by Bolu-Steve, Olawuyi and Gbolade (2017); Okonkwo, Fajonyomi, Omotosho, Esere and Olawuyi (2017) were conducted in Nigeria but not in Gombe State. Although, the previous studies focused on challenges of the children with special needs and specifically on visually impaired but few have examined the coping strategies adopted by these category of students.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The findings of the study revealed that the challenges of students with visual impairment in regular secondary schools include inability to access modern technologies, inappropriate teaching methods and non-availability of special curriculum. The studies by Bolu-Steve, Olawuyi and Gbolade (2017); Okonkwo, Fajonyomi, Omotosho, Esere and Olawuyi (2017) were conducted in Nigeria but not in Gombe State. Although, the previous studies focused on challenges of the children with special needs and specifically on visually impaired but few have examined the coping strategies adopted by these category of students.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Despite this proposed focus on strengths and abilities, and extant policies on 'inclusion' in many countries, by and large, ordinary public institutions are not well-equipped to address the needs of learners with visual impairment in terms of issues such as access to appropriate technology, appropriately modified teaching methods, appropriate learner support nor flexibility in how the curriculum is mediated (Luque et al 2018;Okonkwo et al 2016;Tom, Mpekoa & Swart 2018) and therefore it is necessary to create awareness about these challenges and how they might be addressed. It is recognised that teachers may be hesitant to implement policy based on their own uncertainty and lack of experience in the field (an issue explored later in ch.…”
Section: Ability Versus Disabilitymentioning
confidence: 99%
“…Although the educational rights of students with VI is protected by law in most countries, Turkey included, those rights are unlikely to be upheld fully due to several reasons. It has been similarly reported in the literature that many obstacles exist for students with VI attending classrooms based on inclusion practices (Bardin & Lewis, 2008;Gray, 2009;Metatla, 2017;Morelle, 2016;Morelle & Tabane, 2019;Okonkwo, Fajonyomi, Omotosho Esere, & Olawuyi, 2017;Ramrathan & Mzimela, 2016). Some of these obstacles are a lack of educational services support aimed at classroom teachers, their access to educational materials with Braille or large-font text, and limited access to specialized equipment and assistive technological tools.…”
Section: Introductionmentioning
confidence: 99%